Utilisation of landscape features for overwintering by grassland epigaeic arthropods in timber plantation conservation corridors - Van Deventer, Henno Daniel (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScConsEcol)--Stellenbosch University, 2022.